The Relationship between Nutritional Status and Menstrual Cycle in Adolescent Girls - Anissa Umairah; Tintin Sumarni; Sri Dewi; Aini Yusra; Yulvi Hardoni (CV. CENDIKIA JENIUS INDONESIA, 2024)
Background: A regular menstrual cycle indicates that a woman has good reproductive development and function. On the other hand, an irregular menstrual cycle is one of the signs of menstrual disorders. Factors that can influence changes in the menstrual cycle include nutritional status, as body weight and weight changes affect menstrual function. Objective: The aim of this study is to determine the relationship between nutritional status and the menstrual cycle in adolescent girls. Method: The research design used is observational analytic with a cross-sectional study approach. The population in this study includes all adolescent girls at SMAN 4 Kota Solok, totaling 99 individuals. A sample of 64 individuals met the inclusion and exclusion criteria. Data collection was conducted through interviews and a menstrual cycle questionnaire. Nutritional status was assessed by directly measuring the weight and height of the adolescent girls. Data analysis was performed using the chi-square test (p < 0.05). Results: The results of the study showed that the majority of adolescent girls at SMA Negeri 4 Kota Solok in 2024 had normal menstrual cycles. More than half of the adolescent girls at SMA Negeri 4 Kota Solok in 2024 had a normal BMI. Less than half of the adolescent girls at SMA Negeri 4 Kota Solok in 2024 had underweight/overweight nutritional status with irregular menstrual cycles. After conducting statistical tests, a p-value of 0.215 (p > 0.05) was obtained, indicating that the alternative hypothesis (Ha) was rejected. Conclusion: There is no relationship between nutritional status and the menstrual cycle in adolescent girls at SMA Negeri 4 Kota Solok in 2024.